Estudo de retificadores monofásicos modulares ISOS baseados no conversor flyback - Brito, Bruno Wilson Barbosa de (2020)
This thesis aim’s the operation of two modular flyback converter AC-DC of 200W each with high power factor, connected in series at the input and output, this topology is also known as ISOS – Input-series Output-series. Modularization for converters is the key to reduce stress on components and increase power levels processed by the converter. Some concerns when using techniques such as modularization must be taken só that the converters keep operating balanced and controlled. Usually, voltage and current control are used individually for each converter in order to ensure such balance, but these methods are more expensive and harder to implement. This dissertation brings out an intrinsic characteristic of the AC-DC flyback converter when operated in discontinuous conduction mode, which is the self-balancing among the converter’s voltages, this fact raises interest in several applications for some converters because it eliminates the need for closed-loop controls for voltage and current. This phenomenon has been previously proven and explained in several studies for DC-DC topologies, but the objective is also to prove that the same occurs in AC-DC. The proposed project aims to be simple and has only one control loop for the general output voltage of the two converters to prove that the voltages at the input and output of each converter remain controlled and follow a defined pattern operating in the discontinuous conduction mode. Experimental results showed that the efficiency of this converter reached 92.5%, with a power factor of 0.99 at the nominal power of 400W with a voltage of 400V at the output.